Transcutaneous auricular vagus nerve stimulation alleviates inflammation-induced depression by modulating peripheral-central inflammatory cytokines and the NF-κB pathway in rats - Song, Xingke; Zhu, Haohan; Chen, Zijie; Wang, Yifei; Zhang, Jinling; Wang, Yu; Rong, Peijing; Wang, Junying (Frontiers in Immunology, 2025)
ObjectivesThis study aims to investigate the mechanisms of transcutaneous auricular vagus nerve stimulation (taVNS) in a lipopolysaccharide (LPS)-induced acute inflammatory depression model in rats, focusing on the regulation of peripheral pro- and anti-inflammatory cytokines and the effects on the NF-κB signaling pathway in the prefrontal cortex.MethodsA depressive-like behavior model was established via intraperitoneal injection of LPS, and rats were randomly assigned to a normal group, a model group, and a taVNS intervention group. Behavioral assessments included the sucrose preference test (SPT), open field test (OFT), and elevated plus maze test (EPM) to evaluate depressive-like behaviors. Bio-Plex suspension array technology was used to detect inflammatory cytokine levels in serum, and Western blotting was performed to analyze the expression of NF-κB signaling pathway-related proteins in the prefrontal cortex.ResultsBehavioral tests demonstrated that LPS-induced rats exhibited significant depressive-like behaviors, including reduced sucrose preference, decreased activity levels in the open field, and restricted exploratory behavior in the elevated plus maze. taVNS intervention significantly alleviated these depressive-like behaviors. Serum analysis revealed that pro-inflammatory cytokines (e.g., IL-1β, TNF-α, MCP-1, IL-18, MIP-1α, and MIP-3α) were markedly elevated, while anti-inflammatory cytokines IL-4 and IL-10 were significantly reduced in the model group. taVNS intervention reversed these changes. Western blot analysis showed significant activation of the NF-κB signaling pathway in the model group, characterized by increased p-P65/P65 and p-IκB/IκB ratios and elevated TNF-α expression. taVNS intervention suppressed excessive activation of the NF-κB pathway by reducing p-P65 and TNF-α levels and stabilizing IκB expression.ConclusionsThis study demonstrates that taVNS significantly improves LPS-induced depressive-like behaviors by modulating peripheral pro- and anti-inflammatory cytokine levels and inhibiting the activation of the NF-κB signaling pathway in the prefrontal cortex. These findings highlight the critical role of taVNS in the regulation of the peripheral-central inflammation network and provide theoretical support for the development of taVNS-based non-invasive neuromodulation therapies.